Carbon content and chemical attributes of Oxisol under sugarcane harvested with and without burning - Correia, Benedito Luiz; Alleoni, Luís Reynaldo Ferracciú (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the chemical attributes of a Rhodic Hapludox according to the sugarcane harvest system, with (CQ) and without burning (SQ), in long‑term experiment. In 2009, after 14 years of establishment of a field experiment in Pradópolis, SP, Brazil, soil samples were taken at the planting row, at 0.25 m from the row, and between rows, at 0–0.05, 0.05–0.1, 0.1–0.2, 0.2–0.3, and 0.3–0.4‑m depth. Total organic carbon content (TOC), exchangeable Ca2+, Mg2+ and K+, and resin and Mehlich-1 available P were determined. In general, the SQ system had higher levels of TOC in the row, and at 0.25 from the row, to a depth of 0.3 m. Between lines, the accumulation of carbon was restricted to the first two layers of the soil. SQ system also favored cation exchange capacity and the values of Ca2+, Mg2+, and base saturation, regardless of sampling location, at the first two layers. Available contents of P were little affected by harvesting systems, with higher values found in the CQ system. Harvesting without burning increases carbon accumulation and soil fertility, except for available P.